RANCANG BANGUN SISTEM TELEMETRI DAN MONITORING STASIUN CUACA SECARA NIRKABEL BERBASIS MIKROKONTROLER - Hidayat Nur Isnianto; Esti Puspitaningrum (Jurusan Teknik Informatika, 2012)
Weather system is a facility with instrument for atmospheric physics condition monitoring at certain location and certain time/short period time with daily period maximum. This weather condition is important information in many fields, such as air transportation, voyage, agriculture, national defense, communication, and so on. Therefore it is a necessary to develop a cheap, accurate, and continuous atmosphere condition measurement equipment. This research realizes the telemetry system for monitoring weather elements, such as precipitation, temperature, humidity, wind speed and direction, and sunlight intensity. This system is designed to have transmitter and receiver of weather information. Communication between transmitter and receiver is wireless. At receiver station the information will be processed by microcontroller. Then this weather element information which is measured periodically is displayed. The experiment result shows that the wireless microcontrollerbased system for weather telemetry and monitoring station has errors 1.11% for precipitation, 1.27% for temperature and humidity, 3.05% for air pressure, and 0.61% for light intensity. Optimal distance between the transmitter and the receiver as far as 80 meters.